CACNA1D is a circadian gene and causes familial advanced sleep phase - John M. Webb; Fayal Abderemane-Ali; Liza Ashbrook; Mingyang Ma; Neha Nibber; Xianlin Zou; Maya Yamazaki; Elizabeth Wohler; Nara Sobreira; Daniel L. Minor; Ying-Hui Fu; Louis J. Ptáček (Proceedings of the National Academy of Sciences, 2025)
Familial advanced sleep phase (FASP) is a heritable human sleep trait characterized by early sleep onset and offset times. We have identified five variants in five different families in the human voltage-gated calcium channel subunit alpha1 D ( CACNA1D ) that cosegregate with FASP. The variants in CACNA1D lead to altered channel dynamics in vitro. A mouse model of the E427K variant has a normal circadian period under constant darkness but displays altered phase shifts in response to light in the subjective night at circadian time (CT) 16 and CT22. Overall, these experiments establish CACNA1D as an FASP gene with altered entrainment, highlighting the ability of human genetics to uncover novel aspects of human circadian regulation.